Comparison of normal saline solution with low-chloride solutions in renal transplants: a meta-analysis - Abdullah Jahangir; Syeda Sahra; Muhammad Rafay Khan Niazi; Fasih Sami Siddiqui; Muhammad Yasir Anwar; Ahmad Jahangir; Elie J. El-Charabaty (The Korean Society of Nephrology, 2021)
Background Normal saline solution (NSS) has been the fluid of choice for renal transplant patients, but it can lead to hyperchloremic acidosis and hyperkalemia. This study was performed to compare the safety profile of low-chloride solutions with that of NSS in renal transplant patients. Methods We conducted a systemic review search on PubMed, Embase, and the Central Cochrane Registry. Randomized clinical trials (RCTs) and matched cohort studies involving NSS as the control arm and low-chloride solutions as an intervention arm were chosen. The standardized mean difference for continuous variables, the odds ratio (OR) for discrete variables, and a 95% confidence interval (CI) for effect sizes were used. A p-value of <0.05 was considered statistically significant. Analysis was performed using a random-effects model irrespective of heterogeneity, which was evaluated using I2 statistics. Results Nine RCTs and one cohort study with a total of 726 patients were included. After transplantation, serum potassium was significantly lower in the low-chloride group (standardized mean difference compared to NSS group, -0.38 mEq/L; 95% CI, -0.66 to -0.11; p = 0.007). Similarly, postoperative chloride was lower in the low-chloride group (-2.41 mEq/L [-3.34 to -1.48], p < 0.001). No statistically significance was observed in delayed graft function (OR, 0.98 [0.56-1.69], p = 0.93), day 3 creatinine (-0.14 mg/dL [-0.46 to 0.18], p = 0.38), or day 7 urine output (-0.08 L [-0.29 to 0.12], p = 0.43). Conclusion Use of NSS during renal transplant leads to increased incidence of hyperchloremic acidosis with subsequent hyperkalemia, but clinical significance in the form of delayed graft function or postoperative creatinine remains comparable to that of low-chloride solutions.